Comparison of morphologic changes of rotator cuff muscles following fast isokinetic training and traditional isotonic training in junior state-level weightlifters - Zaini, Siti Salwa Mohamad (2017)
Objective: To evaluate the size of rotator cuff muscles and muscle fiber angle of supraspinatous muscle in two different types of exercise which are fast isokinetic training and traditional isotonic training in state-level weightlifters. Methodology: Subjects (n=16) were recruited through Majlis Sukan Negeri Kelantan. They were gender- and weight- matched and randomly assigned into traditional isotonic training group (TOT) and fast isokinetic training (FIT) group. Both groups went through 24 sessions of training programme three times per week for 8 weeks. MRI was done before the commencement of the training and after the training. MRI of rotator cuff muscles were performed and measurement of CSA and PA were done. Results: CSAs of the four rotator-cuff muscles increased after the intervention programme with significant improvements (p<0.05) found in CSA of supraspinatous muscle (SS) and infraspinatous with teres minor muscles (ISTM), but not in subscapularis muscle (SC). Significant increment in CSAs were found in all rotator-cuff muscles of subjects who underwent FIT but for subjects who underwent TOT, significant increment in CSA was only found in SS, but not that of SC and ISTM. Pennation angle (PA) of the SS significantly increased after the intervention programme. Significant increment in PA was found in all rotator-cuff muscles of subjects who underwent either FIT or TOT. Conclusions: Fast isokinetic training show significant increment of CSAs and PA of the rotator cuff muscles.